RELATIONSHIP AMONG NUTRITIONAL STATUS, BODY FAT PERCENTAGE AND CARDIOVASCULAR FITNESS FOR ADULT INDIVIDUALS. (Fiep Bulletin - online, 2011)
Epidemiological studies conducted recently found changes in lifestyle and eating habits in the last decades due to urbanization and industrialization, resulting in an increase in cases of overweight and obesity. Low or excessive body fat can cause several systemic disorders, and the variation of the anatomical distribution of body fat an important morphological indicator. BP and HR are important parameters in evaluating the cardiovascular system, as their proper maintenance is essential to allow for the exchange of nutrients and excrete the proper functioning of the body. Thus, this research has the main objective correlate indices of nutritional status and body fat percentage to those with the aptitude variables related to cardiovascular health. The research as a descriptive study conducted in the city of Maringá-PR, were evaluated 1323 adults, being 481 women and 842 men. Statistical analysis involved Student t tests, chi-square (X²) and linear correlation coefficient of Pearson (r). Thus, one can observe that BMI scores are positively correlated with indices of blood pressure and %BF with a resting heart rate. Therefore, maintaining a body fat index within the normal range is necessary for the maintenance of health status, as well as for optimal functioning capacity of cardiac work.
Keywords: Nutritional Status; Fitness and Correlation